Comments on the taxonomic validity of Camptodontornis yangi (Li, Gong, Zhang, Yang, and Hou, 2010) and its relationships to Longipteryx chaoyangensis Zhang, Zhou, Hou, and Gu, 2000 and Boluochia zhengi Zhou, 1995 - Yun, Chan-Gyu (Zootaxa, 2019)
Although the nomenclature of the longipterygid bird Camptodontus yangi Li, Gong, Zhang, Yang, and Hou, 2010 may have been clouded by the finding that its generic name was preoccupied by Camptodontus Dejean, 1826 in the carabid beetles, necessitating its replacement by Camptodontornis Demirjian, 2019, the taxonomic status of this species has become even more debatable.